Vasorelaxant and Antihypertensive Effects of Neferine in Rats: An In Vitro and In Vivo Study - Wicha, Piyawadee; Onsa-ard, Amnart; Chaichompoo, Waraluck; Suksamrarn, Apichart; Tocharus, Chainarong (Planta Medica, 2020)
The present study was performed to examine the antihypertensive effect of neferine in hypertensive rats and its relaxant mechanisms in isolated rat thoracic aorta. The antihypertensive effect was evaluated by tail-cuff methods on NG-nitro-L-arginine methyl ester (L-NAME) (40 mg/kg BW) 4-week hypertensive-induced hypertensive rats. The vasorelaxant effect and its mechanisms were studied by the organ bath technique in the thoracic aorta isolated from normotensive rats. The results indicated that the treatment of neferine (1 mg/kg and 10 mg/kg) markedly decreased the systolic blood pressure (SBP) when compared with the hypertension group (137.75 ± 10.14 mmHg and 132.23 ± 9.5 mmHg, respectively, p < 0.001), without affecting the heart rate. Moreover, neferine (10−12 − 10−4 M) exhibited concentration-dependent vasorelaxation in endothelium-intact rings (Emax values = 98.95 ± 0.66% and pD2 = 7.93 ± 0.28) and endothelium-denuded rings (Emax values = 90.61 ± 1.91% and pD2 = 6.85 ± 0.36). The effects of neferine were reduced by pre-incubation with L-NAME and 1H-[1,2,4]oxadiazolo[4,3-a] quinoxalin-1-one (ODQ) but not with pre-incubation with indomethacin and K+channel blockers. Neferine attenuated the contractions induced by phenylephrine and caffeine in a Ca2+-free solution and also inhibited in CaCl2- and phenylephrine-induced contracted rings. Our study suggests that neferine exhibited hypertensive potential, induced vasorelaxation through the endothelium nitric oxide synthase (eNOS)/nitric oxide (NO)/soluble guanylyl cyclase (sGC) pathway and involved the modulation of Ca2+ influx through Ca2+ channels and intracellular Ca2+ release from the sarcoplasmic reticulum.
Keywords: endothelium-dependent; endothelium-independent; hypertension; neferine; nelumbonaceae; Nelumbo nucifera; rat aorta vasorelaxation